Fatal Pulmonary Infection with Mycobacterium celatum in an Apparently Immunocompetent Patient - Bux-Gewehr, Irene (American Society for Microbiology, 1998)
Mycobacterium celatum is a recently described mycobacterium isolated from patients who have suppressed cell-mediated immunity, such as AIDS. We present here, to our knowledge, the first report of a fatal pulmonary infection caused by M. celatum in a 73-year-old immunocompetent female patient. The mycobacterium was identified by a 16S rRNA sequence analysis.